Abduction or detention of a minor or a helpless person in the light of art. 211 of the Criminal Code - MAJKRZAK, KATARZYNA (Prawo Kanoniczne, 2017)
In the article 211 of the Criminal Code in the catalog of offenses against family and care, the legislator stated that anyone who, against the will of a person appointed to care or supervision, abduct or detain a minor under the age of 15 or mentally or physically helpless person shall be subject to the penalty of deprivation of liberty of 3 months up to 5 years. Institution of care and supervision is the legal and statutory protection. At the same time care and supervision are provided for the proper development and well-being of a minor or helpless person. The crime implies the effect of deprivation of legitimate care or supervision over a minor below the age of 15 or a helpless person.